COACHING STYLE IN MANAGEMENT EDUCATOR’S WORK WITH C-LEVEL MBA PARTICIPANTS - Maltsev, Eduard; Sapozhkova, Olena (The Modern Higher Education Review, 2025)
This article substantiates a coaching style of teaching as an effective approach in executive MBA (C-level) programs. It introduces the CQA-Executive (Content–Question–Action) model and a learning micro-cycle tailored to executives’ profiles, characterised by high expertise and selectivity, limited time and opportunity cost, ROI orientation, and sensitivity to practical value and confidentiality. The model sequences concise expert input with reflective, managerial questioning that anchors concepts in participants’ strategic challenges, followed by application-in-action and formative feedback. A typology of questions is specified (goal clarification, experience questions, assumption-surfacing, options generation, commitment-to action, reflective questions). Class activities include decision labs, peer-advisory triads, case sprints, and reflective journaling. Assessment integrates transparent success criteria and three-layer feedback (feed up, feedback, feed forward) with transfer metrics (30–60–90-day action plans, speed of decision making, accountability check-ins, self-assessment of effectiveness). The framework aligns with theories of adult, experiential, and reflective learning, as well as with Ukrainian scholarship on educational coaching. Expected benefits include autonomy support, stronger self-efficacy, higher engagement, and faster decisions with improved workplace transfer. Boundary conditions, faculty development needs, and assessment alignment are discussed. The paper presents a rigorous yet pragmatic approach for integrating coaching micro-practices into executive-level lectures, cases, and projects, without compromising overall academic standards or curricular coherence.